Misdiagnosed fibrosarcoma of the mandible mimicking temporomandibular disorder: a rare condition - NAMDAR PEKİNER, FİLİZ MEDİHA (MOSBY-ELSEVIER, 2007)
The jawbones can be sites of various neoplastic conditions. Given the variety of processes affecting this particular anatomical area, formulation of a precise diagnosis can be challenging to clinicians. Limited jaw movement, pain, and facial asymmetry are common signs among patients, especially those with temporomandibular disorder ( TMD). This paper reports a case of primary fibrosarcoma affecting the mandible and surrounding structures in a 14-year- old girl presenting signs and symptoms similar to TMD. Her condition was misdiagnosed, and she was treated for TMD over an extended period before the correct diagnosis was made for fibrosarcoma. The patient underwent surgical resection with postsurgical radiotherapy and chemotherapy and now is being followed up. Although malignant lesions are rare in the temporomandibular joint ( TMJ) region, dentists are advised to be aware of the condition and to keep in mind that patients who are admitting for TMD can also possibly be affected from neoplasms. Hence, those patients have to be examined meticulously to avoid misdiagnosis and mistreatment.
Keywords: NASOPHARYNGEAL CARCINOMA; SOFT-TISSUE